Penerapan Konsep Teori Belajar Behaviorisme Pada Pembelajaran Pendidikan Agama Islam di Sekolah Dasar - Ahmad Nanda Maulana; Tarsono; Risma Nurlela; Kiki Miftahul Hakiki; Chikoko, Vitallis (Educompassion: Jurnal Integrasi Pendidikan Islam dan Global, 2025)
This study aims to examine the application of behaviorism theory in the learning of Islamic Religious Education at the elementary school level as an effort to shape students' religious behavior. A behaviorist approach that focuses on the relationship between stimulus and response emphasizes that learning is the result of observable and measurable behavioral changes. This study uses a literature study method by examining the basic concepts and principles of behaviorism which include habituation, positive and negative reinforcement, and punishment as a systematic learning strategy. The results of the study show that the application of behaviorism theory in PAI learning is effective in improving discipline, forming habits of behavior according to Islamic teachings, and strengthening students' ability to apply religious values in daily life. These findings confirm that behaviorism has a strong relevance to the educational goals of PAI in the early stages of child development. Thus, behavioristic approaches are recommended to be continuously optimized by educators through a learning design that is contextual, sustainable, and oriented towards Islamic character formation.